2006
DOI: 10.1002/ajmg.a.31076
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in Costello syndrome

Abstract: Costello syndrome (CS) was initially described by Costello in 1971; it is caused by a germline mutation in HRAS proto-oncogene. The aim of the present study was to evaluate the respiratory activity during sleep in a group of subjects with CS. We studied 10 consecutive patients, 4 males and 6 females, aged 3-29 years, affected by CS. All patients underwent clinical, neurological, otholaryngologic and radiologic evaluation, and a full-night polysomnography in the sleep laboratory. Polysomnography showed that sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Furthermore, the observation of changing endoscopic findings in this case suggests that the natural course of the respiratory status depends on the underlying mechanism of upper airway obstruction. Della Marca et al [31] found a high prevalence of upper airway obstruction in patients with Costello syndrome. They …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observation of changing endoscopic findings in this case suggests that the natural course of the respiratory status depends on the underlying mechanism of upper airway obstruction. Della Marca et al [31] found a high prevalence of upper airway obstruction in patients with Costello syndrome. They …”
Section: Discussionmentioning
confidence: 99%
“…Group I cases required adequate clinical description and/or photograph. We excluded reviews with limited prenatal history (Lin et al, 2002; Axelrad et al, 2004; Gripp et al, 2005; Aoki et al, 2005; Della Marca et al, 2006; Axelrad et al ., 2007; Schulz et al ., 2008), and mosaicism (Gripp, et al 2006; Sol-Church et al, 2009). We mailed a data collection form to the parents of HRAS mutation positive patients who had been enrolled in an ongoing natural history study of Costello Syndrome (Group III), and also included 3 additional cases cared for by authors..…”
Section: Patientsmentioning
confidence: 99%
“…36,37 Seven of 10 individuals ages 3-29 years undergoing polysomnography in the sleep laboratory had obstructive events. 38 Dental abnormalities, including enamel defects, occur frequently. Excessive secretions are often noted.…”
Section: Introductionmentioning
confidence: 99%